Two new species of Timea from the Southwest Atlantic (Timeidae, Demospongiae, Porifera) - Leite, Dora M. B.; Fonseca, Cássio A.; Leal, Camille V.; Hajdu, Eduardo (Zootaxa, 2015)
Comprising 56 species, Timea Gray, 1867 belongs to the monotypic family Timeidae Gray, 1867, with both family and genus characterized by the presence of (sub)tylostyles as megascleres, and euasters as microscleres. Two new species are described from the coast of Rio de Janeiro state, Timea berlincki sp. nov. and Timea clandestina sp. nov., the first of which also from São Paulo state (southeastern Brazil). Both are compared to other species based on their morphological and skeletal characters. Records of all species of the genus worldwide are tabulated and discussed, and an identification key for Tropical western Atlantic species of Timea is offered.